Pierre Loeb. - Musée d'Ixelles (Ixelles : Musée d'Ixelles, 1979)
Arp, Jean ; Artaud, Antonin ; Balthus ; Berard, Christian ; Bolin, Gustave ; Calder, Alexandre ; Domelia-Nieuwenhuis, César ; Dufour, Bernard ;Dufy, Raoul ; Ernst, Max ; etc.
Pierre Loeb, Musée d'Ixelles, 4 oct. - 23 déc '79
boek